Role of plant hormones in flowering and exogenous hormone application in fruit/nut trees: a review of pecans - Amandeep Kaur; Niels Maness; Louise Ferguson; Wei Deng; Lu Zhang (Fruit Research, 2021)
Pecan is the only native north American tree nut. The USA produces approximately 80% of the world’s pecans. Pecan trees have an extended juvenility, 10 years to the first nut crop. With mature bearing they begin alternate bearing; alternating large and small crops. Theoretically, a heavy crop inhibits flower induction in the current year resulting in a low crop the following year. The flowering of perennial trees involves a complex interplay of multiple hormones. The possible molecular mechanisms regulating tree flowering can be revealed by endogenous plant hormone quantification, exogenous hormone application and RNA-sequencing. In this review, we synthesize the investigations of transcriptomic analysis and exogenous hormone treatments on bud break and flowering in fruit/nut trees with a focus on pecan. Knowledge of how hormones regulate flowering suggest they are a potential tool for improving return bloom and mitigating alternate bearing.